PENERAPAN METODE QAWAID WA TARJAMAH PADA KETERAMPILAN QAIRA’AH DAN KITABAH KELAS V SDI AL HADAD KEDUNGJAMBE SINGGAHAN TUBAN - Mu’allimah, Siti Khofifatul; Anisah, Zulfatun; Ulya, Vita Fitriatul (Al Ulya: Jurnal Pendidikan Islam, 2023)
This research aims to explain the Qawaid wa tarjamah method for qiraah and kitabah skills in Arabic language subjects for class V SDI Al Hadad Kedungjambe Singgahan Tuban. Qualitative research as a method in this research. Three techniques include observation,pinterviews and documentation. The research resultshshow that applying the Qawaid wa tarjamah method in learning Arabic can improve reading, writing and translation skills. From the results of applying the qawaid wa tarjamah method, many class V students at SDI Al Hadad Kedungjambe Singgahan Tuban have reached thehKKM. The KKM score that must be achieved is 70. There are 85% or 29 studentspwho are able to achieve the KKMuscore and 15% or 5 students whohhave not been able to achieve the KKM score. Supporting factors in implementing this method include the presence of nahwu shorof learning, guru who have teaching skills, and ustaz/guru who can condition the class well. Meanwhile, the inhibiting factor in implementing this method is that students are often noisy and chat to themselves, so that students experience delays in reading and writing Arabic.